Nutrition and physical activity randomized control trial in child care centers improves knowledge, policies, and children’s body mass index - Alkon, Abbey (BioMed Central, 2014)
BACKGROUND: To address the public health crisis of overweight and obese preschool-age children, the Nutrition And Physical Activity Self Assessment for Child Care (NAP SACC) intervention was delivered by nurse child care health consultants with the objective of improving child care provider and parent nutrition and physical activity knowledge, center-level nutrition and physical activity policies and practices, and children’s body mass index (BMI). METHODS: A seven-month randomized control trial was conducted in 17 licensed child care centers serving predominantly low income families in California, Connecticut, and North Carolina, including 137 child care providers and 552 families with racially and ethnically diverse children three to five years old. The NAP SACC intervention included educational workshops for child care providers and parents on nutrition and physical activity and consultation visits provided by trained nurse child care health consultants. Demographic characteristics and pre - and post-workshop knowledge surveys were completed by providers and parents. Blinded research assistants reviewed each center’s written health and safety policies, observed nutrition and physical activity practices, and measured randomly selected children’s nutritional intake, physical activity, and height and weight pre- and post-intervention. RESULTS: Hierarchical linear models and multiple regression models assessed individual- and center-level changes in knowledge, policies, practices and age- and sex-specific standardized body mass index (zBMI), controlling for state, parent education, and poverty level. Results showed significant increases in providers’ and parents’ knowledge of nutrition and physical activity, center-level improvements in policies, and child-level changes in children’s zBMI based on 209 children in the intervention and control centers at both pre- and post-intervention time points. CONCLUSIONS: The NAP SACC intervention, as delivered by trained child health professionals such as child care health consultants, increases provider knowledge, improves center policies, and lowers BMI for children in child care centers. More health professionals specifically trained in a nutrition and physical activity intervention in child care are needed to help reverse the obesity epidemic. TRIAL REGISTRATION: National Clinical Trials Number NCT01921842